(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Work Motivation isa set of energetic forces that originate both within and beyond being anindividual, to initiate work-related behavior and to determine its form,direction, intensity and duration. Work motivation is given by the ratio ofrewards and performance, as these types of incentives are given to merit orrecognition based on tasks assigned. If the management of a company wants topenalize an employee because he has made a mistake (unjustified absence, theft)a disciplinary measure must be taken. However, its implementation should not bediscretionary. Overall, the rewards system has been found to be an effective toolof employee retention and motivation. But, the punishment system has not foundmuch success and leads to resentment and negativity in employees. This researchexplores the various reactions given by employees towards rewards andpunishments given in organisations.